Psicoterapia grupal: benefícios dessa assistência aos usuários e a instituição - Orpheu, Helenice Barreiros; Moreno, Vânia [UNESP] (My University, 2013)
The present study is about an investigation that used as methodological strategy the systematic review. A literature review was carried out in the database of the Scientific Electronic Library Online. Six articles, on Group Psychotherapy, were selected to evaluate the contribution of scientific research published in national periodicals during the period 2007 to 2012. From the data analysis, two categories emerged: Benchmarks and Group Psychotherapy in Clinic and Health Services.

Trata-se de uma investigação que utilizou como estratégia metodológica a revisão sistemática. Foi realizado um levantamento bibliográfico na base de dados da Scientific Eletronic Library Online. Seis artigos foram selecionados a partir da questão que permeou o estudo, qual seja, conhecer a contribuição das investigações científicas publicadas nos periódicos nacionais no período de 2007 a 2012 sobre a psicoterapia grupal. A partir da análise de dados emergiram duas categorias: marcos referenciais e a psicoterapia grupal na prática clínica e nos serviços de saúde.
Group psychotherapy: benefits of this assistance to the users and institution
Keywords: Group psychotherapy; Health services; Clinic; Psicoterapia grupal; Serviços de saúde; Prática clínica